CALCULATION OF THE UV ABSORPTION SPECTRA OF AS(III) OXO- AND THIO- ACIDS AND ANIONS IN AQUEOUS SOLUTION AND OF PF3 IN THE GAS-PHASE - Tossell J.A. (My University, 2001)
Changes in the UV spectra of As(OH)3 solutions with variations in pH and temperature have recently been used to determine the temperature dependence of the pKa of the acid. In previous studies I used quantum mechanical techniques to study changes in structure and vibrational spectra as a function of pH for arsenites and thioarsenites. I previously calculated UV spectra for ``molecular'' minerals, like realgar As4S4. Here I use a number of different quantum mechanical methods, both Hartree-Fock and density functional theory based, to calculate the UV spectra for both a related simple well-characterized gas-phase molecule PF3 and for As(OH)3 and As(SH)3 and their conjugate anions and some neutral and anionic oligomers in aqueous solution. For the monomeric species small numbers of water molecules have been explicitly included, in a supermolecule or microsolvation approach. I find that UV absorption energies accurate to a few tenths of an eV can be obtained both for gas- phase PF3 and for neutral arsenious acid in aqueous solution, for which the UV absorption maximum is calculated to occur around 6.5 eV, consistent with experiment. Accurate calculation of the UV energies for arsenite anions in aqueous solution is much more difficult, since basis set size and solvation effects are considerably larger than for the neutral molecules, but fairly reliable results can still be obtained. Deprotonation is found to reduce the lowest calculated UV transition energy by about half an eV. Oligomerization also reduces the lowest calculated UV energy by at least half an eV. Replacement of one or all the -OH groups by -SH groups reduces the lowest calculated UV energies by about 2 eV. UV excitation energies have been calculated for oligomeric species as large as As3E3(EH)3 and As4E6, where E = O, S, and may be useful for identifying such species in solution.
Keywords: UV SPECTRA; OXOACIDS; THIOACIDS; ARSENITES; QUANTUM CALCULATIONS